Interfacing carbon quantum dots with scheelite and wolframite MWO4 (M = Ca, Cu, Co): Structural insights toward enhanced photo- and electrocatalytic performance - Şimsek, Esra Bilgin; Firtina-Ertis, Irem; Özdemir, Ercan (Elsevier B.V., 2025)
This study focuses on the development of carbon quantum dot (CQDs)-decorated metal tungstates (MWO4, where M = Ca, Cu, Co) to assess their photocatalytic and electrocatalytic performance. Scheelite-(CaWO4) and wolframite-type (CuWO4, CoWO4) structures were synthesized and modified with CQDs via a one-pot hydrothermal method. The resulting composites were thoroughly characterized using XRD, SEM-EDX, TEM, UV–vis DRS, PL, and EIS techniques. Morphological and compositional studies confirmed successful integration of CQDs onto the tungstate surfaces. Optical characterization revealed that CQDs modification enhanced visible-light absorption in wolframite-type tungstates and effectively suppressed electron–hole recombination, as evidenced by photoluminescence quenching. The photocatalytic activities of the materials were investigated through the degradation of doxycycline under visible light. Among the catalysts, CuWO4/CQDs exhibited the highest degradation efficiency, with a kinetic rate constant 6.49 times greater than that of pristine CuWO4. The enhanced performance was attributed to improved light harvesting, better charge separation, and increased surface oxygen vacancies facilitated by CQDs. In parallel, electrocatalytic oxygen evolution reaction (OER) performance was evaluated. Linear sweep voltammetry and Tafel analyses demonstrated significant improvement in electrocatalytic activity upon CQD incorporation. Notably, CoWO4/CQDs showed the lowest onset potential and Tafel slope (49.67 mV/dec), highlighting its superior charge-transfer kinetics. Overall, this work presents the first systematic comparison of CQD-modified scheelite and wolframite tungstates, revealing critical structure–property relationships. The findings offer valuable insights for the design of multifunctional CQD–tungstate composites for sustainable environmental and energy applications. © 2025 Elsevier B.V., All rights reserved.
Keywords: CaWO4; CoWO4; CQDs; CuWO4; Degradation; Electrocatalysis; Photocatalysis